Mobile Devices-aware Refactorings for Scientific Computational Kernels - Rodriguez, Ana (2012)
The increasing number of mobile devices with ever-growing processing capabilities, make them interesting for scientific applications development. However, we must take into account that mobile devices still have limited capabilities compared to fixed devices. Besides, mobile devices rely on battery as energy supply. For these reasons, this paper analyzes different micro-benchmarks battery consumption given by common operations in scientific computational kernels. Indirectly, we propose good programming practices or code refactorings in order to minimize mobile devices battery consumption.